DESIGNING THE STRATEGY OF STUDENT INDIVIDUALITY IN INDEPENDENT RESEARCH ACTIVITY (JournalNX - A Multidisciplinary Peer Reviewed Journal, 2023)
This article describes the essence of scientific research on the problem of organizing students' independent research activities. In it, special attention is paid to the theoretical foundations of organizing students' independent research activities, the forms, methods and means of organizing this process. Pedagogical and psychological aspects of organizing students' independent research activities and criteria for determining the level of formation of students' independent work skills and qualifications are discussed.